(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2015)
Libya has an infinite water resource available in the coastal towns and cities being located on Mediterranean Sea with 1950km coast. Therefore, the need for desalinated water for Nuclear Research Center NRC located in Tajura is currently about 1200 m 3 /day. To cover the center present and future water needs for research and development activities, two thermal sea water desalination plants have been assembled in the site. One of the plants uses Multi Stage Flash technology and the other one uses Multi Effect Desalination technology with capacity of 1200m /day each one. Detailed design for 1200m 3 /day seawater reverse osmosis SWRO unit is carried out using ROSA S oftware to make the technical comparison with other MSF and MED units. The unit labeled an S W30XLE-440i by the results of the Software is selected since it required the lower feed pressure of 55.5bar and highest salt recovery of 45% with total dissolved solid of 190ppm. From the technical point of view, the study showed that SWRO required lower sea water inlet flow rate than MSF and MED. The units efficiency are 43%, 10.5% and 25% for SWRO, MSF, and MED, respectively. Further the Product quality TDS 190ppm for RO unit is suitable for drinking water, while those of MSF and MED 50ppm. Energy consumption as heating steam is not required for the S WRO unit; however, a steam flow rate 7.3m 3/hr is required by MSF and MED units. These make SWRO unit friendlier to the environment and most proper technically under these situations.